Analisis Pengaruh Budaya Organisasi terhadap Produktivitas Karyawan melalui Pelatihan dan Pengalaman Kerja - Fikri, Fikri; Nursi, Mulyadi (Universitas Negeri Makassar, 2025)
This study aims to analyze the influence of organizational culture on employee productivity through training and work experience at CV Risba Production Bandung, West Java. This study used a quantitative approach with a sample size of 100 employees, and data were collected through a questionnaire using a 1–5 Likert scale. Data analysis was conducted using PLS-SEM to test the relationships between variables and the mediation of training and work experience.The results showed that organizational culture had a positive and significant effect on training and work experience. Furthermore, training and work experience had a positive effect on employee productivity. Mediation analysis revealed that organizational culture also had an indirect effect on productivity through training and work experience, with partial mediation. These findings emphasize the importance of an organizational culture that supports employee competency development and experience as a strategy to increase productivity.This study provides implications for company management to continue strengthening an organizational culture that supports training and work experience, and to develop structured employee development programs.